Pengaruh Kepercayaan Merek, Personal Selling dan Kepuasan Pelanggan terhadap Loyalitas Pelanggan pada Amaris Hotel Setiabudhi Bandung - Al Fitra Nugraha; Intan Widuri Sakti (Wawasan : Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2026)
This study aims to analyze the influence of brand trust, personal selling, and customer satisfaction on customer loyalty at Amaris Hotel Setiabudhi Bandung. The background of this study is the declining trend of customer loyalty indicators at the hotel, marked by a drop in room occupancy from 81.54% in 2023 to 68.92% in 2025. The research method used is quantitative with descriptive and verificative approaches. Data were collected through questionnaires distributed to 100 respondents selected using purposive sampling. Data analysis was conducted using multiple linear regression with the assistance of SPSS. The results showed that brand trust, personal selling, and customer satisfaction each have a positive and significant partial effect on customer loyalty. Personal selling proved to be the most dominant variable, with a regression coefficient of 0.527 and the highest t-value of 4.179. Simultaneously, the three variables explain 71.7% of the variation in customer loyalty (R² = 0.717). These findings indicate that customer loyalty at Amaris Hotel Setiabudhi Bandung is strongly shaped by the quality of direct staff-customer interactions, brand credibility, and overall service satisfaction.